Gambaran Penerimaan Diri Pada Ibu yang Mengalami Keguguran Akibat Stress Kehilangan Pekerjaan - Khalil Firza Ardiansyah; Zahwa Afrida Fazrina; Muhammad Iqbal (Jurnal Ners, 2025)
Job loss remains a major source of stress for women, even if they have a partner who also works. As a mother, the psychological stress of losing a job role can have an impact on emotional and physical conditions, and can even increase the risk of pregnancy. Miscarriage is an emotionally challenging experience, both psychologically and physically for both parents. Self-acceptance is the psychological process of someone accepting and appreciating themselves as a whole, including their strengths, weaknesses, and all aspects of themselves. This study aims to explore the process of self-acceptance in a mother. The research subject with the initials ZZ, aged 54 years, is a mother who experienced a miscarriage due to stress caused by job loss. There are 3 informants, namely the subject's husband, the subject's close friend, and the subject's child. In the context of a mother who experienced a miscarriage due to stress due to job loss, self-acceptance has a very big influence on the challenges in her to face the problem. This study applies a qualitative method by conducting semi-structured interviews with a mother who experienced a miscarriage due to stress due to job loss. The results showed that the subject experienced emotional stress due to job loss and hunger. Through family support, a spiritual approach, and reconstruction of hope, the subject was able to accept the conditions she experienced. Subject self-acceptance is formed through self-understanding, realistic expectations, and a supportive environment.